2021
DOI: 10.1186/s12886-021-02086-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of optic neuritis treatment trial (ONTT) combined corticosteroid regimen on pattern reversal visual evoked potentials: a prospective follow-up study

Abstract: Background The combined corticosteroid regimen of the original Optic Neuritis Treatment Trial (ONTT) is used in many centers to treat optic neuritis. Though pattern reversal visual evoked potentials (PRVEPs) are a sensitive, standard measure of visual conduction in optic neuritis, no studies hitherto have investigated the effect of combined ONTT regimen on PRVEPs. We aimed to determine the effect of combined corticosteroid regimen of the ONTT on changes of PRVEPs in patients with first-episode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We followed up 44 patients. Among them, 29 patients have been treated with optic neuritis treatment trial combined corticosteroid regimen, while 15 patients have been conservatively managed [20].…”
Section: Resultsmentioning
confidence: 99%
“…We followed up 44 patients. Among them, 29 patients have been treated with optic neuritis treatment trial combined corticosteroid regimen, while 15 patients have been conservatively managed [20].…”
Section: Resultsmentioning
confidence: 99%
“…Given that VEPs were not used as an outcome measure in this ONTT study, or even in other studies done in this regard to assess the efficacy of combined corticosteroid treatment, pattern reversal VEPs (PRVEP) have been used to assess the short-term recovery of visual conduction pathways in a cohort of Sri Lankan patients with optic neuritis who underwent treatment with combined ONTT regimen [9][10][11][12]. In this follow up study, interestingly, it was observed that there is a marked trend of improvement in P100 latency values in PRVEP in affected eyes in the ONTT combined regimen treated group immediately one month after the treatment, and further improvement was observed in 3 months after the pre-treatment, baseline assessment [13]. Therefore, it can be assumed that ONTT combined regimen could have accelerated the rate of recovery faster as shown by the original ONTT.…”
Section: What Is the Current Status Of Visual Electrophysiology In Sri Lanka?mentioning
confidence: 87%